Shifts in the gut microbiota of sea urchin Diadema antillarum associated with the 2022 disease outbreak - Ruiz-Barrionuevo, Juliana M.; Kardas, Elif; Rodríguez-Barreras, Ruber; Quiñones-Otero, Marcos A.; Ruiz-Diaz, Claudia P.; Toledo-Hernández, Carlos; Godoy-Vitorino, Filipa (Frontiers in Microbiology, 2024)
Caribbean coral reefs have lost many vital marine species due to diseases in recent decades. The well-documented mass mortality event of the long-spined black sea urchin Diadema antillarum in the early 1980s stands out among these collapses. This die-off, with an unknown pathogen(s), killed over 90% of D. antillarum changing the reefscape from coral to algal-dominated. Nearly 40 years later, D. antillarum populations have yet to recover. In early 2022, a new mortality event of D. antillarum was reported along the Caribbean, including Puerto Rico. This study identifies the gut microbiota changes associated with the D. antillarum during this mortality event and contrasts them with the bacterial composition of gut samples from healthy individuals collected in 2019. Notably, the die-off group's core microbiome resembled bacteria commonly found in the human skin and gut, suggesting potential anthropogenic contamination and wastewater pollution as contributing factors to the 2022 dysbiosis. The animals collected in 2022, especially those with signs of disease, lacked keystone taxa normally found in healthy Diadema including Photobacterium and Propionigenium. The association between human microbes and disease stages in the long-spined urchin D. antillarum, especially in relation to anthropogenic contamination, highlights a complex interplay between environmental stressors and marine health. While these microbes might not be the direct cause of death in this species of sea urchins, their presence and proliferation can indicate underlying issues, such as immune depletion due to pollution, habitat destruction, or climate change, that ultimately compromise the health of these marine organisms.